Transdiagnostic and unique mechanisms of health anxiety, panic disorder, and obsessive-compulsive disorder - Byam, Layton (My University, 2022)
The present study examined the transdiagnostic and unique mechanisms that may be associated with health anxiety (HA), panic disorder (PD), and obsessive-compulsive disorder (OCD) symptoms. A non-clinical university sample (N = 549) completed measures of HA, PD, and OCD symptoms. Participants also completed measures of anxiety sensitivity, disgust propensity and sensitivity, intolerance of uncertainty, metacognitions related to health, and body vigilance. Each of these mechanisms moderately to strongly correlated with the symptom scales. A multiple regression analysis was conducted for each symptom scale. Anxiety sensitivity was found to be a transdiagnostic predictor of HA, PD, and OCD. The metacognitive belief that thinking positively about one's health will lead to negative outcomes was associated with both PD and OCD. Additionally, body vigilance was associated with both HA and PD. Unique factors associated with HA were HA-specific intolerance of uncertainty and the metacognitive belief that thoughts are uncontrollable. PD was associated with PD-specific intolerance of uncertainty. Lastly, OCD was associated with OCD-specific intolerance of uncertainty, depression-specific intolerance of uncertainty, and disgust sensitivity. The findings demonstrate that while HA, PD, and OCD share transdiagnostic mechanisms, each can be distinguished by disorder-specific mechanisms. Therapists may wish to target both transdiagnostic and disorder-specific mechanisms in their treatment plan when working with clients presenting HA, PD, or OCD symptoms.
Presented on May 12-13, 2022 at the 12th Annual Canadian Association of Cognitive and Behavioural Therapies Virtual Conference held at Simon Fraser University in Vancouver, British Columbia.
Keywords: anxiety disorders; panic disorders; illness anxiety disorder; obsessive-compulsive disorder